In vivo Dopamine Efflux is Decreased in Striatum of both Fragment (R6/2) and Full-Length (YAC128) Transgenic Mouse Models of Huntington's Disease - Callahan, Joshua W.; Abercrombie, Elizabeth D. (Frontiers in Systems Neuroscience, 2011)
Huntington's disease (HD) is characterized by numerous alterations within the corticostriatal circuitry. The striatum is innervated by a dense array of dopaminergic (DA) terminals and these DA synapses are critical to the proper execution of motor functions. As motor disturbances are prevalent in HD we examined DA neurotransmission in the striatum in transgenic (tg) murine models of HD. We used in vivo microdialysis to compare extracellular concentrations of striatal DA in both a fragment (R6/2) model, which displays a rapid and severe phenotype, and a full-length (YAC128) model that expresses a more progressive phenotype. Extracellular striatal DA concentrations were significantly reduced in R6/2 mice and decreased concomitantly with age-dependent increasing motor impairments on the rotarod task (7, 9, and 11 weeks). In a sample of 11-week-old R6/2 mice, we also measured tissue concentrations of striatal DA and found that total levels of DA were significantly depleted. However, the loss of total DA content (<50%) was insufficient to account for the full extent of DA depletion in the extracellular fluid (ECF; ∼75%). We also observed a significant reduction in extracellular DA concentrations in the striatum of 7-month-old YAC128 mice. In a separate set of experiments, we applied d-amphetamine (AMPH; 10 μm) locally into the striatum to stimulate the release of intracellular DA into the ECF. The AMPH-induced increase in extracellular DA levels was significantly blunted in 9-week-old R6/2 mice. There also was a decrease in AMPH-stimulated DA efflux in 7-month-old YAC128 mice in comparison to WT controls, although the effect was milder. In the same cohort of 7-month-old YAC128 mice we observed a significant reduction in the total locomotor activity in response to systemic AMPH (2 mg/kg). Our data demonstrate that extracellular DA release is attenuated in both a fragment and full-length tg mouse model of HD and support the concept of DA involvement in aspects of the syndrome.